The Role of Green Entrepreneurship and Green Variables in Sustainable Development in the Culinary Sector in Indonesia: Early Days of the COVID-19 Pandemic - Helin G. Yudawisastra; Mokhammad Anwar; Sulaeman R. Nidar; Yudi Azis (Universitas Pasundan, 2022)
The UN Sustainable Development Goals are among the crucial missions of countries worldwide, including Indonesia. Nevertheless, application of a production system does not guarantee sustainability, and the Indonesian government’s support for sustainability in the entrepreneurial sector is nonoptimal. This study investigates green entrepreneurship in Indonesia’s culinary sector in relation to sustainable development and green variables. Using a culinary sector survey based on the UNWTO and the Ministry of Tourism, this study references primary questionnaire data, applying a random sampling technique and structural equation modeling covariance with a sample of 270 respondents. The results indicate that the provision of green products affects sustainable development, regardless of respondents’ green entrepreneurship. While green products may affect sustainable development, directly or through green entrepreneurship, green design does not appear to affect sustainable development, and green entrepreneurship does not appear to support sustainable conditions. Environmentally friendly product design and production processes have generated multiple recyclable products; however, the culinary sector must be made aware of the entrepreneurial ecosystem surrounding culinary business governance and the concerns and practices of sustainable development. This study was conducted at the beginning of the COVID-19 pandemic and represents the conditions of the culinary sector during the pandemic.